Analyzing the Ideal Leadership of Prophet Yusuf in the Quran: Relevance to Transformational Leadership Theory - Hakim, Lukman; Mustaqim, Mustaqim; Hadi, Abd (TAFSE: Journal of Qur'anic Studies, 2024)
This study delves into the Quranic concept of ideal leadership by examining the narrative of Prophet Yusuf and its alignment with transformational leadership theory. Utilizing a qualitative library research approach, this analysis synthesizes insights from an array of primary and secondary sources including classical Islamic texts and contemporary scholarly articles. It identifies key leadership qualities exemplified by Prophet Yusuf such as intellectual prowess, professionalism, fairness, consistency, and the capacity to nurture a productive and inclusive environment. These attributes are juxtaposed with Bernard M. Bass's transformational leadership framework, which comprises intellectual stimulation, inspirational motivation, individualized consideration, and idealized influence. The research articulates how the leadership exemplified by Prophet Yusuf resonates with modern theoretical constructs and offers practical implications for contemporary leadership in organizational and national contexts. The findings underscore the enduring relevance of Quranic narratives in informing and enhancing modern leadership paradigms.